Study of Criminology on Minor as a Theft Offender (Study on Sukoharjo, Central Java, Indonesia) - Al Rosyid, Azis; Karismawan, Yogi; Gumilar, Hertantyo Rizky; Chabibun, Anas; Setiawan, Sadam Agus (Law Research Review Quarterly, 2019)
Theft in the modern era is very common today. Theft is carried out not only by adults, but small children or underage people also commit theft. Internal factors and external factors are factors that greatly influence the child's mindset and behavior towards this world. Law enforcement for a child who is confronted needs to be done for the sake of upholding the law. An action carried out by a small child or an underage person has a cause which is the background of why the action was carried out. This is where the important role of crimininology is in knowing why someone committed a crime and how to overcome the problem of crime. The role of family, community, peers, and schools is very important to monitor the behavior patterns of children